METHODOLOGY OF DEVELOPMENT OF INDEPENDENT LEARNING PROCESSES IN GEOMETRY TEACHING - Rasulova Gulnozakhan Azamovna; Ochilova Dilnavoz Ulugbek qizi (Researchparks Publishing, 2023)
This article highlights issues related to organizing independent learning in the teaching process of geometry, based on students' individual and reflexive experiences. It discusses didactic games and problem-solving approaches aimed at shaping and developing skills. The article emphasizes the clear representation of problems on diagrams, various methods of utilizing different tools, as well as the integration of information communication tools and conceptual recommendations to address related issues. The establishment and implementation of independent learning processes in geometry, based on the paradigm of personalized education trends, and the organization of geometry lessons using technologies for shaping and conducting lessons according to students' individual preferences and connections with interdisciplinary areas are also discussed.